Women in global trade: Challenges faced by STEM micro, small, and medium-sized enterprises in Chile - Campillay, Paula (Latin American Journal of Trade Policy, 2024)
Globally, advancements in trade have benefited millions of women, but assuming that these benefits are distributed equitably between men and women would be a mistake. However, market opening has not generated equitable benefits between men and women, raising questions about the inequalities that limit female participation in trade (WTO, 2020). Given that most female economic activity is in micro, small, and medium enterprises (MSMEs), implementing strategies to promote women’s participation in trade involves examining how MSMEs can integrate into commercial activities (WTO, 2020). Therefore, it is essential to have studies that identify the barriers preventing the full participation of women-owned businesses in international markets. In the current context, it is essential to explore the challenges faced by STEM micro, small, and medium enterprises (MSMEs) led by women in Chile. This study identifies four main obstacles: gender biases in the business environment, harmonization between family and professional responsibilities, limited availability of financing, and temporal discrepancy between technological advancements and current regulations. A nivel global, los avances en el comercio han beneficiado a millones de mujeres, pero asumir que estos beneficios se distribuyen equitativamente entre hombres y mujeres sería un error. Sin embargo, la apertura de los mercados no ha generado beneficios equitativos entre hombres y mujeres, planteando interrogantes sobre las desigualdades que limitan la participación femenina en el comercio (OMC, 2020). Dado que la mayor parte de la actividad económica femenina se encuentra en las micro, pequeñas y medianas empresas (MIPYME), la implementación de estrategias para promover la participación de las mujeres en el comercio implica examinar cómo las MIPYME pueden integrarse en las actividades comerciales (OMC, 2020). Para ello, es fundamental contar con estudios que identifiquen cuáles son las barreras que impiden una plena participación de las empresas de mujeres en los mercados internacionales. En el presente contexto, resulta esencial explorar los desafíos a los que se enfrentan las micro, pequeñas y medianas empresas (MIPYME) STEM dirigidas por mujeres en Chile. Este estudio identifica cuatro obstáculos principales: los sesgos de género presentes en el entorno empresarial, la armonización entre las responsabilidades familiares y profesionales, la limitada disponibilidad de financiamiento y la discrepancia temporal entre los avances tecnológicos y las regulaciones actuales.